Pollution, green union and network industry - Luciano Fanti; Domenico Buccella (Kiel Institute for the World Economy (IfW), 2018)
In this paper the authors investigate whether and how, in a network industry, the intensity of network effects affect the total pollution under the presence of a union interested to "local" environmental damages (e.g. polluting production processes damaging workers' health and the local environment where workers live). Under monopoly, it is shown that network effects tend to increase, on the one hand, the investments in the cleaning technology but, on the other hand, the polluting output, so that their effects on the total pollution are theoretically ambiguous. In particular, the authors find that total pollution is reduced (resp. increased) with increasing network effects intensity if the market is sufficiently large (resp. small). Moreover the pollution-reducing result of the increasing network effect is more likely when the existing network effects, the union's environmental concerns and the technological efficiency are sufficiently large. These findings are qualitatively confirmed also under different union's preferences, Government's environmental standard and Cournot duopoly, and thus offer interesting empirical as well as policy implications.
Keywords: J51; L12; 330; network goods; cleaning technology; pollution production; green unions; monopoly; Cournot duopoly